(untitled) (Comparative & International Education Series, 2021)
This chapter focuses on an exploration of the effects and implications of COVID-19 on the case study of Hong Kong community colleges. Comparisons are made with US and other global counterparts as well. The liberal education that community colleges deliver traditionally depends on the concept of dynamic learning community, featuring liberal teacher-student interactions and pedagogic environment, learner-centered formative assessment, effective student services for strategic university articulation, and dynamic student activities and engagement (Tang & Dang, 2019). In the case of Hong Kong, a small community college campus in Hong Kong that serves as a hub of geographic location where the above-mentioned activities take place in real time. In late 2019, it was unprecedented that COVID-19 made Hong Kong’s community colleges close their campus and moved teaching, learning and assessment completely online. This chapter engages in the case study of Hong Kong’s community colleges in view of how it mitigated COVID-19 through organizational adaptation and sustained the delivery of liberal education, especially when social protests and global pandemic may persist in upcoming times.